Antibacterial, antibiofilm, and photocatalytic activities of metals-substituted spinel cobalt ferrite nanoparticles. (February 2019) - Maksoud, M.I.A. Abdel; El-Sayyad, Gharieb S.; Ashour, A.H.; El-Batal, Ahmed I.; Elsayed, Mohamed A.; Gobara, Mohamed; El-Khawaga, Ahmed M.; Abdel-Khalek, E.K.; El-Okr, M.M.
Abstract: This study reports the photocatalytic degradation of Methylene Blue (MB) dye (a class of dyestuffs that are resistant to biodegradation) under the influence of UV-light irradiation. Antibacterial and antibiofilm activities of ferrite nanoparticles (FO NPs) were examined against some pathogenic bacteria isolated from the medical operating room surfaces. In the same context, metals-substituted spinel cobalt ferrite nanoparticles with nominal composition [Mx Co1-x Fe2 O4 NPs; (M = Zn, Cu, Mn; x = 0.0, 0.25, 0.5 and 0.75)] were synthesized by citrate sol-gel method. Also, the structures of the synthesized FO NPs were characterized by X-ray diffraction, and Williamson-Hall (WH) method was used to determine the crystallite size. The estimated specific surface area is found in the range from 37.99 to 107.05 m 2 /g, between the synthesized ferrites, Zn0.5 Co0.5 Fe2 O4 NPs have average pore radius 1.84 nm and the pore volume was 0.136 ml/g. SEM images revealed that, the synthesized FO NPs have an unique pores and uniformly distribution, while EDX spectra shows the elemental composition for the synthesized FO NPs. The elastic properties of FO NPs have been estimated using FTIR data, whereas (M − H) hysteresis loops revealed that, by replacing cobalt ions with Zn, Cu, and Mn ions the magnetic behaviour changed from ferromagnetic to paramagnetic. Results obtained from the photocatalysis indicated that Mn0.75 Co0.25 Fe2 O4 NPs (30.0 mg) were a promising photocatalyst achieving 96.0% removal of MB after 100 min of UV-light exposure in the alkaline solution. Antibacterial results showed that the most effective combination was Zn0.75 Co0.25 Fe2 O4 NPs (20.0 ppm) displaying activity against Staphylococcus aureus, Enterococcus columbae, and Aerococcus viridians by 15.0, 13.0, and 12.0 mm ZOI, respectively. Additionally, Zn0.75 Co0.25 Fe2 O4 NPs were active as antibiofilm factors producing activity by 63.7, 57.9, and 45.5% towards S. aureus, A. viridians, and E. columbae, respectively. Accordingly, Zn0.75 Co0.25 Fe2 O4 and Mn0.75 Co0.25 Fe2 O4 NPs can be utilized in industrial, biological and medical applications. Graphical abstract: Image 1 Highlights: Citrate sol-gel mediates synthesis of metals-substituted spinel CFO NPs. Morphological, elemental, crystal, and magnetic characterization. Antibacterial and antibiofilm evaluation. Photocatalytic degradation of MB estimation. Promising nano-material for industrial, environmental, and biomedical applications.